2014
DOI: 10.5751/ace-00624-090104
|View full text |Cite
|
Sign up to set email alerts
|

Off-road sampling reveals a different grassland bird community than roadside sampling: implications for survey design and estimates to guide conservation

Abstract: ABSTRACT. Grassland bird species continue to decline steeply across North America. Road-based surveys such as the North American Breeding Bird Survey (BBS) are often used to estimate trends and population sizes and to build species distribution models for grassland birds, although roadside survey counts may introduce bias in estimates because of differences in habitats along roadsides and in off-road surveys. We tested for differences in land cover composition and in the avian community on 21 roadside-based su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…However, other investigators have noted significant differences for some species in the number of individuals detected between on‐road and off‐road points (Wellicome et al. ), but found that counts along narrow secondary roadways (such as those associated with BBS routes) lessen this bias (Hutto et al. ).…”
Section: Methodsmentioning
confidence: 98%
“…However, other investigators have noted significant differences for some species in the number of individuals detected between on‐road and off‐road points (Wellicome et al. ), but found that counts along narrow secondary roadways (such as those associated with BBS routes) lessen this bias (Hutto et al. ).…”
Section: Methodsmentioning
confidence: 98%
“…Finally we suggest that investigation of factors that affect birds density or suitability be based on surveys from inside the farms, rather than counting along roads (e.g. Wellicome et al 2014). Habitat on road verges often does not resemble habitat within farms and birds nesting along road verges may be more exposed to predation (Wellicome et al 2014) and may suffer more from disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Wellicome et al 2014). Habitat on road verges often does not resemble habitat within farms and birds nesting along road verges may be more exposed to predation (Wellicome et al 2014) and may suffer more from disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Construction of any road removes vegetation and typically changes adjacent vegetation type and height, resulting in widespread changes to grassland vegetation alongside roads and across the landscape (e.g. Wellicome et al 2014). Ditches are associated with many roads, and vegetation grows taller and more dense in ditches because of greater local moisture levels, thus supporting greater small mammal populations (Poulin 2003).…”
Section: Discussionmentioning
confidence: 99%